(untitled) (Research, Society and Development, 2020)
The objective was the genetic selection of cassava (Manihot esculenta crantz) to formation of groups. Initially, 23 quantitative variables from 28 genotypes were used. After principal-components analysis, this number was reduced to 7 variables (stalk diameter, number of maniva-seed per plant, root length, root diameter, leaf water potential in the morning, leaf water potential in the midday and produtivity of aerial part. A cluster analysis using Chebyshev distance and Mcquitty connection methods were used to generate a dendrogram whose validation was based from cophenetic coefficient of 0.8. Two groups composed of 24 and 4 cassava genotypes were formed. These were indicated in the dendrogram using Ratkowsky, McClain and KL indexes. The second group formed by the tussuma, Caititi, Poti Branca and mulatinha genotypes showed higher frequency of the variables that describe an upper part of cassava. This information is important for the creation of database for rustic species and their improvement.